On Representation of Solutions of Abstract Fractional Differential Equations - Balachandran, K.; Lizzy, R. Mabel; Trujillo, J. J. (Journal of Applied Nonlinear Dynamics, 2026)
In this paper we discuss about the solution representation of abstract fractional differential equations with different conditions on the operator A. The solution representation obtained by using Mittag-Leffler function is correct when the operator A is bounded. However when the operator A is unbounded the representation derived in [1] seems to be incorrect. We also obtain a suitable form of solution to stochastic fractional differential equation with unbounded operators.